2009
DOI: 10.1063/1.3112009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid simulation of the E-H mode transition in inductively coupled plasma

Abstract: One self-consistent method combined with the electromagnetic theory and fluid model is developed to investigate the E-H mode transition of argon inductively coupled plasma (ICP) by adjusting the external electric parameters of the reactor. ICP dynamic characteristics of radial and axial space are also studied when E and H modes coexist. By regulating the radio-frequency current in the coil and voltage across the powered end of the coil and the ground, the E-H mode transition is observed, accompanied by the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Comparison with Ref. 25 shows that the selection of the uniform conductivity indeed generates a more reasonable field structure, especially for a capacitive field. We believe that the omission of the spatial variation in the conductivity parameter will not significantly influence the main results, since very similar mode transitions are observed for both forms of the conductivity.…”
Section: A Electromagnetic Modulementioning
confidence: 92%
See 2 more Smart Citations
“…Comparison with Ref. 25 shows that the selection of the uniform conductivity indeed generates a more reasonable field structure, especially for a capacitive field. We believe that the omission of the spatial variation in the conductivity parameter will not significantly influence the main results, since very similar mode transitions are observed for both forms of the conductivity.…”
Section: A Electromagnetic Modulementioning
confidence: 92%
“…Nevertheless, to preserve the validity of the separation of variables method, the spatially averaged, instead of the spatially resolved, conductivity was used. In our previous work, 25 the spatial conductivities were directly input into the field equations, based on the local approximation used in that paper. In the present work, the spatial conductivity is replaced by this volume mean value.…”
Section: A Electromagnetic Modulementioning
confidence: 99%
See 1 more Smart Citation
“…This behavior can be explained theoretically. Zhao et al27 employed the electromagnetic theory with local-density approximation to simulate the electromagnetic field distribution in ICPs. They found that the radial component of the azimuthal field in the plasma region is related to the Bessel functionsFIG.…”
mentioning
confidence: 99%
“…Therefore, development of an analysis method for Inductively-Coupled Plasma (ICP) in the lamp is effective to design the suitable lamp shape. Although some simulation K. Kakehashi is with the Panasonic Electric Works Information Systems Co.,Ltd., 1048, Kadoma, Osaka, 571-8686, Japan method for ICP were reported [4][5][6] II. ANALYSIS PROCEDURE , analysis target of them is RF-driven ICP such as plasma process and ion engine.…”
Section: Introductionmentioning
confidence: 99%